Analytical Heat Transfer Second edition - Han, Je-Chin (Taylor & Francis, 2022)
Analytical Heat Transfer explains how to analyze and solve conduction, convection, and radiation heat transfer problems. It enables students to tackle complex engineering heat transfer problems prevalent in practice. Covering heat transfer in high-speed flows and unsteady highly turbulent flows, the book also discusses enhanced heat transfer in channels, heat transfer in rotating channels, numerical modeling for turbulent flow heat transfer, and thermally developing heat transfer in a circular tube. The second edition features new content on Duhamel's superposition method, Green's function method for transient heat conduction, finite-difference method for steady state and transient heat conduction in cylindrical coordinates, and laminar mixed convection. It includes two new chapters on laminar-to-turbulent transitional heat transfer and turbulent flow heat transfer enhancement, in addition to end-of-chapter problems. The book bridges the gap between basic heat transfer undergraduate courses and advanced heat transfer graduate courses for a single semester of intermediate heat transfer, advanced conduction/radiation heat transfer, or convection heat transfer. Features: Focuses on analyzing and solving classic heat transfer problems in conduction, convection, and radiation Covers 2-D and 3-D view factor evaluation, combined radiation with conduction and/or convection, and gas radiation optically thin and optically thick limits Features updated content and new chapters on mass and heat transfer analogy, thermally developing heat transfer in a circular tube, laminar-turbulent transitional heat transfer, unsteady highly turbulent flows, enhanced heat transfer in channels, heat transfer in rotating channels, and numerical modeling for turbulent flow heat transfer Provides step-by-step mathematical formula derivations, analytical solution procedures, and demonstration examples Includes end-of-chapter problems with an accompanying Solutions Manual for instructors This book is ideal for undergraduate and graduate students studying basic heat transfer and advanced heat transfer.